Does Remittance Receiving Households Prepared against Natural Disasters in Nepal? - Chaudhary, Gangadhar; Timsina, Tatwa Prasad (Journal of Advanced Academic Research, 2018)
The study examines the perception of remittance receiving families to consume its portion of income on building capacity and preparedness against any natural disasters in Nepal. Moreover, there is growing evidence that remittance income is consumed to improve livelihood, especially on household expenses, education, treatment and the construction of the new house or repairing existing one. The objective of this study is to analyze to what extent the poor people whose earning incomes, including remittance, prepare them to cope with the upcoming natural disasters to minimize the loss afterward. The sites were purposefully selected in different districts in Nepal to observe the way of preparedness and have vulnerable to natural disaster. The snowball sampling method was chosen to interview with open and closed questionnaires only to remittance receiving families. Similarly, the observation method was used to assess the quality and type of houses they belong. The qualitative data were processed using SPSS 20 with statistical tools as frequencies and verified with one way ANOVA test. The result showed that the remittance receiving families improved their livelihood (improving their living standard with more expenses in home, health, and education, construction, savings) It was observed that the remittance receiving families consumed income in new construction of houses and repairing to make their houses strong without consulting the technical expert or use of building codes, that rising doubt to withstand the worse impact of natural disasters mainly earthquake, flood and landslide. This study concludes that the remittance receiving household, though have better livelihood, yet they are not better prepared against the ruthless impact of any natural disasters.